(untitled) (Archives of The Medicine and Case Reports, 2024)
Neonatal asphyxia remains a significant contributor to neonatal mortality and morbidity globally. Identifying maternal and neonatal predictors of asphyxia is crucial for developing targeted interventions to improve neonatal outcomes. This study aimed to investigate the association between various maternal and neonatal factors and the occurrence of asphyxia in newborns at Salatiga Regional General Hospital. A case-control study was conducted at Salatiga Regional General Hospital from January 1st to December 31st, 2023. Cases were newborns diagnosed with asphyxia based on an Apgar score ≤ 6 at 5 minutes. Controls were newborns without asphyxia. Data on maternal factors (premature rupture of membranes, mode of delivery, maternal age, parity, and gravidity) and neonatal factors (birth weight and gestational age) were collected from medical records. Bivariate and multivariate analyses were performed to assess the associations between these factors and asphyxia. The study included 234 newborns (117 cases and 117 controls). Bivariate analysis revealed significant associations between asphyxia and premature rupture of membranes (p = 0.027), mode of delivery (p = 0.000), birth weight (p = 0.000), and gestational age (p = 0.000). Multivariate logistic regression analysis identified the mode of delivery (OR = 83.468, 95% CI: 18.624-374.079) and birth weight (OR = 69.576, 95% CI: 8.781-551.277) as independent predictors of asphyxia. Cesarean section and low birth weight are significant predictors of neonatal asphyxia. These findings highlight the importance of careful consideration of delivery mode and close monitoring of newborns with low birth weight to prevent and manage asphyxia effectively.